PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA DI SMP NEGERI 2 TONDANO - Girsang, Try Putri Sriayu; Suriani, Ni Wayan; Rungkat, Jovialine A (LPPM Politeknik Saint Paul Sorong, 2024)
This study examines how student learning outcomes in human digestive system material at SMP Negeri 2 Tondano are impacted by the Children Learning in Science (CLIS) learning model. The purpose of this study is to determine how student learning results pertaining to topics linked to human digestion are influenced by the Children Learning In Science (CLIS) learning model. This study was conducted at SMP Negeri 2 Tondano during the odd semester of the 2023–2024 academic year.This study is an experimental endeavor. The participants in this study are class VIII students of SMP Negeri 2 Tondano. Two classes are used in this study: Class VIII B, which has 19 students as a control group, and Class VIII A, which has 20 students as an experimental group. Data on student learning outcomes from both learning models were generated via the pretest and posttest. According to the study's findings, the experimental class scored an average of 27.75 on the pretest and 80.75 on the posttest, compared to the control class's average of 25.26 on the pretest and 41.58 on the posttest. When using a comparison test to evaluate the hypothesis, Ho is rejected and Ha is accepted when the significance value is less than 0.05. This demonstrates that when using the Children Learning In Science (CLIS) learning paradigm instead of traditional learning methods, pupils achieve superior results. This study discovered that student learning outcomes relating human digestion were influenced by the Children Learning In Science (CLIS) learning paradigm at SMP Negeri 2 Tondano.